2011
DOI: 10.1186/cc10100
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cells (EPC) in sepsis with acute renal dysfunction (ARD)

Abstract: IntroductionSepsis is characterized by systemic microvascular dysfunction. Endothelial progenitor cells (EPCs) are critically involved in maintaining vascular homeostasis under both physiological and pathological conditions. The aim of the present study was to analyze the endothelial progenitor cell system in patients suffering from sepsis with acute renal dysfunction.MethodsPatients with newly diagnosed sepsis were recruited from the ICU in a nonrandomized prospective manner. Blood samples were obtained withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 40 publications
6
63
0
3
Order By: Relevance
“…We observed a 3-fold higher level of cEPCs in hantavirus disease patients than in the healthy control group. In septic patients, the number of cEPCs is 2 to 4 times that in healthy controls (31,32). The increase in cEPC numbers seems to indicate a mobilization of progenitor cells due to hantavirus-induced endothelial damage.…”
Section: Patient Characteristicsmentioning
confidence: 88%
See 1 more Smart Citation
“…We observed a 3-fold higher level of cEPCs in hantavirus disease patients than in the healthy control group. In septic patients, the number of cEPCs is 2 to 4 times that in healthy controls (31,32). The increase in cEPC numbers seems to indicate a mobilization of progenitor cells due to hantavirus-induced endothelial damage.…”
Section: Patient Characteristicsmentioning
confidence: 88%
“…For example, multiple organ failure in sepsis is a consequence of altered endothelial function due to infection and the subsequent host response. Recently, several studies have identified the key role of EPCs in the outcome of severe sepsis (30)(31)(32). The number of cEPCs in septic patients correlates with survival and inversely with the severity of the clinical course.…”
mentioning
confidence: 99%
“…Recent studies have also shown that circulating EPCs are associated with human sepsis (9,10). In two studies, patients with sepsis were found to have increased numbers of circulating EPCs by flow cytometry compared with control subjects (10,34).…”
Section: Original Articlementioning
confidence: 99%
“…MiRNA-126, -34a, -155, and -125b expression in serum exosomes were determined by realtime PCR. Lung permeability was determined using Evans blue dye as previous described (30 EPCs in peripheral blood were determined as described (10). Cells were stained with the following antibodies: FITC-antimouse-CD34 antibody (eBioscience, San Diego, CA) and PE-antimouse-FLK-1 (BD Biosciences, San Diego, CA).…”
Section: Clpmentioning
confidence: 99%
“…An increased number of circulating EPCs was detected in ARDS patients and correlated with improved survival [101]. However, in septic individuals endogenous EPCs showed reduced proliferative, adhesive, migratory and angiogenic capacities [102,103]. Experimentally, two different approaches were performed to maintain the beneficial effects of EPCs.…”
Section: Stem Cell Based Approaches In Lung Injurymentioning
confidence: 99%